The Prevalence of Adverse Childhood Experiences in Ohio: Changes from 2015 to 2019 - Geoffrey Carney-Knisely; Kraig J. Knudsen; Joshua Orack; Jessica Linley (Ohio Journal of Public Health, 2024)
Background: Adverse childhood experiences (ACEs) are associated with long-term negative health outcomes including substance use and mental health disorders. Little is known about how exposure to ACEs impacts health care access in adulthood. Methods: We examined the prevalence of ACEs in 2015 and 2019 in Ohio. We analyzed relationships between ACEs and self-reported health outcomes, with a focus on health care access and utilization. We examined the 2015 and 2019 Behavioral Risk Factor Surveillance System (BRFSS) data from 14 247 persons who resided in Ohio. We stratified participants by ACE prevalence and assessed demographic differences between groups. Multivariable and multinomial logistic regression models were used to analyze health-related outcomes of interest. Results: The prevalence of experiencing any ACE increased from 2015 to 2019, from approximately 62% to 68%. Exposure to ACEs was associated with smoking (OR = 3.167), binge drinking (OR = 3.259), and heavy drinking (OR = 4.455). Persons with any ACEs had increased odds of no health insurance (OR = 1.435) and increased odds of not having a doctor for any reason (OR = 1.722). Persons with 3 ACEs had 4.307 times the odds of depression, and this increased to 8.250 among persons with 5 or more ACEs. There was no association between ACEs and hypertension, cancer, heart attacks, stroke, and diabetes. Conclusion: These findings support the hypothesis that ACEs have a long-term effect on health and access to health care. Findings from this study may inform interventions to reduce the incidence and long-term sequelae of ACEs.
Keywords: ACEs; Mental health; Health care utilization; Health care access; Epidemiology